Genetic mapping of sexually dimorphic volatile and non-volatile floral secondary chemistry of a dioecious willow. (17th June 2022) - Keefover-Ring, Ken; Carlson, Craig H; Hyden, Brennan; Azeem, Muhammad; Smart, Lawrence B
Abstract : Secondary chemistry mediates many important ecological interactions and often differs between sexes in dioecious plant species; however, its genetic basis is not well known for many species. Abstract: Secondary chemistry often differs between sexes in dioecious plant species, a pattern attributed to its possible role in the evolution and/or maintenance of dioecy. We used GC-MS to measure floral volatiles emitted from, and LC-MS to quantitate non-volatile secondary compounds contained in, female and male Salix purpurea willow catkins from an F2 family. Using the abundance of these chemicals, we then performed quantitative trait locus (QTL) mapping to locate them on the genome, identified biosynthetic candidate genes in the QTL intervals, and examined expression patterns of candidate genes using RNA-seq. Male flowers emitted more total terpenoids than females, but females produced more benzenoids. Male tissue contained greater amounts of phenolic glycosides, but females had more chalcones and flavonoids. A flavonoid pigment and a spermidine derivative were found only in males. Male catkins were almost twice the mass of females. Forty-two QTL were mapped for 25 chemical traits and catkin mass across 16 of the 19 S. purpurea chromosomes. Several candidate genes were identified, including a chalcone isomerase associated with seven compounds. A better understanding of the genetic basis of the sexually dimorphic chemistry of a dioecious species may shed light on how chemically mediated ecological interactions may have helped in the evolution and maintenance of dioecy.